Synthesis and Dielectric-Antimicrobial Properties of Poly(n-Butyl Methacrylate) with Chalcone Initiator - Coşkun, Demet (Adiyaman University, 2025)
In this study, in the first stage, the chalcone compound was synthesized in accordance with the literature. Then, the synthesized chalcone compound was reacted with bromine acetylbromide and the initiator used in the ATRP method was synthesized. The characterization of the synthesized compound was carried out by FT-IR and NMR spectrometers. The number average molecular weight (Mn) of the polymer was measured as 11780 and the heterogeneity index (HI) was measured as 1.32 by Gel Permeation Chromatography (GPC). In the second stage, the synthesized chalcone compound was used as an initiator and the polymerization of n-butyl methacrylate monomer was provided by the ATRP method. In the last stage, the dielectric and antimicrobial properties of the polymer were investigated. The Agar well method was used in the antimicrobial study. Dielectric properties were investigated as a function of frequency between 100 Hz and 5000 Hz at room temperature. © 2025, Adiyaman University. All rights reserved.
Poli(n-Bütil Metakrilat)'ın Kalkon Başlatıcısı ile Sentezi ve Dielektrik-Antimikrobiyal Özellikleri
Keywords: Antimicrobial properties; ATRP; Chalcone; Dielectric properties